2017
DOI: 10.7717/peerj.3580
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mortality and socioeconomic status on risk and delayed rewards: a replication with British participants

Abstract: Here, we report three attempts to replicate a finding from an influential psychological study (Griskevicius et al., 2011b). The original study found interactions between childhood SES and experimental mortality-priming condition in predicting risk acceptance and delay discounting outcomes. The original study used US student samples. We used British university students (replication 1) and British online samples (replications 2 and 3) with a modified version of the original priming material, which was tailored t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…In humans, the prevailing finding has been for greater risk aversion with chronological ageing (Harbaugh et al 2002; Deakin et al 2004; Dohmen and Falk 2010; Mohr et al 2010; Boyle et al 2011; Rutledge et al 2016; although see Cavanagh et al 2012; Pachur et al 2017), a pattern similar to that in our starlings in respect of our biomarker of biological ageing. Increased risk aversion was also observed in human experimental participants primed to perceive greater extrinsic mortality risk, and therefore potentially perceive lowered life expectancy (Pepper et al 2017). However, a single study in humans examining the association between risk preference and telomeres found greater risk proneness in a stock investment task to be associated with shorter telomere length (Yim et al 2016).…”
Section: Discussionmentioning
confidence: 95%
“…In humans, the prevailing finding has been for greater risk aversion with chronological ageing (Harbaugh et al 2002; Deakin et al 2004; Dohmen and Falk 2010; Mohr et al 2010; Boyle et al 2011; Rutledge et al 2016; although see Cavanagh et al 2012; Pachur et al 2017), a pattern similar to that in our starlings in respect of our biomarker of biological ageing. Increased risk aversion was also observed in human experimental participants primed to perceive greater extrinsic mortality risk, and therefore potentially perceive lowered life expectancy (Pepper et al 2017). However, a single study in humans examining the association between risk preference and telomeres found greater risk proneness in a stock investment task to be associated with shorter telomere length (Yim et al 2016).…”
Section: Discussionmentioning
confidence: 95%
“…To the extent that not having enough money to meet one's needs triggers this basic sense of resource scarcity, it should cause regulatory and cognitive priorities to shift toward the most immediate financial concerns, at the cost of long-term economic outcomes. This logic can help us make sense of the finding that the lower one's SES, the more likely one is to exhibit signs of apparent failures in self-regulation, such as impulsivity, future discounting, and poor planfulness (24) (1), and that reminders of economic scarcity lead to present-biased financial decisions among those who grew up in families experiencing financial strain (25) (though see (26)). On this account, it is not that early life or adult exposure to adversity diminishes self-regulatory capacity (8,27), but that it shifts regulatory priorities toward meeting short-term goals (see (28)(29)(30)(31)).…”
Section: Low Ses Cues Resource Scarcitymentioning
confidence: 99%
“…Our search for interactive influences is motivated by previous research. For example, Nettle and Bateson (2017) found that the negative health effects of low adult socioeconomic position were more marked if individuals had experienced childhood deprivation; and Griskevicius et al (2011) found that a current cue of environmental adversity had different effects on the impulsivity of people who had experienced different levels of childhood deprivation (though see Pepper et al 2017).…”
Section: Introductionmentioning
confidence: 99%